2013
DOI: 10.1002/lary.23986
|View full text |Cite
|
Sign up to set email alerts
|

Phase of nasal cycle during sleep tends to be associated with sleep stage

Abstract: Nasal cycle duration during sleep is longer than in wakefulness. Changes in laterality of nasal cycle frequently coincide with switches in posture, tend to occur in REM sleep, never occur in slow-wave sleep, and may be absent in subjects with severe nasal septal deviations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 19 publications
5
46
1
1
Order By: Relevance
“…This study confirms that the side of maximal nasal airflow is influenced by body position, with the most airflow occurring through the uppermost nasal cavity 19 . In addition, the data support the notion that the nasal cycle is not an artifact of asymmetrical body position or other environmental factors 20,21,22 . Since no asymmetries in body pressure and posture were present when subjects were in the supine position, the airflow from this position may be most representative of the endogenous nasal cycle 23 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This study confirms that the side of maximal nasal airflow is influenced by body position, with the most airflow occurring through the uppermost nasal cavity 19 . In addition, the data support the notion that the nasal cycle is not an artifact of asymmetrical body position or other environmental factors 20,21,22 . Since no asymmetries in body pressure and posture were present when subjects were in the supine position, the airflow from this position may be most representative of the endogenous nasal cycle 23 .…”
Section: Discussionsupporting
confidence: 75%
“…Haight and Cole 24 , while providing evidence for the nasal cycle during sleep, were unable to demonstrate a clear relationship between sleep stage and nasal cycle phase since measurements were made after the patients were aroused from sleep. Kimura et al 22 found an association between the reversal of the nasal cycle and sleep stage in 69% of 16 subjects studied. None of the reversals occurred in the slow-wave sleep.…”
Section: Discussionmentioning
confidence: 94%
“…Next, we used individual PSG signal processing to evaluate stage-specific breathing abnormalities (i.e., OSA during rapid-eye-movement [REM] sleep stage) as previously described. 11 Given that REM sleep is characterized by significant nasal congestion 12,13 and that REM sleep modulates the nocturnal phenotypical features of OSA in asthmatic children, 11 we postulated that children with rhinitis and OSA would have more REM-related breathing abnormalities relative to those with OSA alone.…”
mentioning
confidence: 99%
“…The status of airflow dominance between the right and left nasal airways is correlated with sympathetic and parasympathetic dominant states, respectively, as regulated by the ANS, 53,54 the lateralised ultradian rhythm of alternating cerebral hemispheric dominance 55,56 and is tightly coupled to sleep staging 44,46,53,55,57,58 and sleep position. 59 This suggests that the nasal cycle is strongly connected with sympathovagal balance.…”
Section: Nasal Cycle and The Autonomic Nervous Systemmentioning
confidence: 99%
“…60 The RACer-PAP technology artificially reinstates nasal cycle patterns throughout sleep which is postulated to have a positive effect on sleep state architecture. 9,27,29,33,34,35,36,37,38,53 A polysomnographic sleep clinic pilot study has recently been conducted with three n-CPAP-compliant OSA sufferers who received breathing treatment pressures ranging from 8 cm H 2 O to 14 cm H 2 O. This study compared treatment efficacy during full overnight use of RACer-PAP and n-CPAP systems.…”
Section: Rest-activity-cycler Treatmentmentioning
confidence: 99%